Determination of structure of precursor of ibuprofen: purification and analysis - Abdul Jalil, Aishah; Kurono, Nobuhito; Tokuda, Masao (2004)

(untitled)
(S)-2-(p-isobutylphenyl) propanoic acid, so called ibuprofen, is one of the most popular anti-inflammatory agents. An efficient cross-coupling reaction of organozinc compound of ethyl 2-bromoacrylate, prepared by the reaction of hightly reactive zinc was carried out with aryl iodide to synthesize 2-(4-isobutylphenyl)-propenoate, a precursor of ibuprofen. Highly reactive zinc metal (EGZn/Naph) was readily prepared by electrolysis of a DMF solution containing naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. The synthesized precursor of ibuprofen was purified by thin layer chromatography on silica gel and its structure was confirmed by elemental analysis, mass, IR, 1H NMR and 13C NMR spectroscopic analysis.